Minimum required distance for clinically significant measurement of habitual gait speed - Myung Woo Park; Sun Gun Chung; Jaewon Beom; Kyung Su Kim; Joonghee Kim; Chul-Hyun Park; Jinkyu Lee; Keewon Kim (BMC Geriatrics)
Abstract Background Gait speed indicates morbidity and life expectancy in older adults, but the minimum walking distance for measurement remains unclear. This study aimed to determine the minimum distance required to measure clinically reliable gait speed using a smartphone camera and pose estimation, and whether the distance is influenced by subject characteristics or measurement methods. Methods Twenty-four healthy volunteers (≥ 65 years old) performed a video-recorded 10-m gait test, including acceleration and deceleration. Fourteen body points were derived using a pose-estimation algorithm. Speed was calculated based on the center of mass or a leading foot which simulates a condition with a walkway sensor and validated against manual measurements. Multiple videos of gait over varying distances were obtained by cropping video frames at 0.1-m intervals. Variance in gait speed over specific distances was calculated using ANOVA. “Minimum required distance” was defined as the shortest distance where the confidence interval of gait speed did not exceed the minimal clinically important difference (0.1 m/sec). We also investigated which clinical, anthropometric, or epidemiological variables might influence it by assessing their association with gait speed variance using mean squared error from linear regression. Results Gait speed measured by pose estimation (1.55 ± 0.18 m/s) showed a high level of agreement with manual measurement (1.56 ± 0.14 m/s), with an intraclass correlation coefficient of 0.889 (95% CI: 0.822–0.931). “Minimum required distance” was 2.1 m when gait speed was calculated with the center of mass with 95% confidence interval while “minimun required distance” based on a leading foot was 4.7 m with 90% confidence interval. Gait speed itself and muscle strength were positively correlated with gait speed variance (r = 0.250, p = 0.036 for gait speed; r = 0.312, p = 0.008 for knee extension strength; r = 0.230, p = 0.053 for grip strength), whereas other epidemiologic or clinical parameters, and physical performance scales, were not. Conclusions Clinically reliable measurement of gait speed could be achieved over 2.1 m using a smartphone and pose estimation inducing the center of mass with 95% confidence interval. The weaker the muscle strength or the slower the gait speed, the shorter the distance might be required.